(untitled) (Journal of Enam Medical College, 2016)
Background: In chronic kidney disease (CKD) intact parathyroid hormone (iPTH) level is often increased before clinical hyperphosphatemia occurs. Despite its importance very few studies evaluated parathyroid status in CKD. Objective: The study was undertaken to estimate level of parathormone in diabetic CKD patients at a tertiary level hospital and assessing its relationship with different parameters like hemoglobin, calcium etc. and comparing biochemical and clinical variables between normal parathyroid and hyperparathyroid groups. Materials and Methods: It was a hospital based cross-sectional study involving purposively selected chronic kidney disease patients attending nephrology and endocrinology outdoor and indoor services of BIRDEM hospital, Dhaka, Bangladesh. Study was conducted during the period of April to October 2010. All the subjects were divided into two groups based on serum parathormone level and different parameters were compared between groups. Results: The mean duration of chronic kidney disease was significantly higher in hyperparathyroid group than that in the normal group (<0.001). Retinopathy and hypertension were more common in hyperparathyroid group than that in patients with normal serum parathormone (p<0.001 and p=0.012). Neuropathy was solely present in hyperparathyroid group (p<0.001). Mean fasting blood glucose, serum creatinine and serum phosphate were significantly higher in the hyperparathyroid group compared to normal group (p<0.001 in all cases) while the mean serum calcium and haemoglobin were lower in hyperparathyroid group than those in the normal group (p<0.001 in both cases). Serum creatinine and serum parathormone bears a significantly linear relationship (r=0.986, p<0.001), while serum parathormone and serum calcium bears a significantly negative relationship (r=?0.892 and p<0.001). Conclusion: Earlier intervention on the basis of iPTH in addition to other biochemical parameters of chronic kidney disease is recommended. J Enam Med Col 2016; 6(3): 140-147